Differences in the Dwell Time of Peripherally Inserted Central Catheters between Patients with Catheter Colonization and Those Developing Central Line-Associated Bloodstream Infection: A Single Centre Retrospective Cohort Study - Vassiliki C. Pitiriga; Elsa Campos; John Bakalis; George Saroglou; Athanasios Tsakris (MDPI AG, 2024)
Substantial knowledge gaps exist concerning the varying durations of peripherally inserted central catheter (PICC) placements that lead to either central line-associated bloodstream infection (CLABSI) or catheter colonization. We aimed to compare PICCs dwell time between patients who developed CLABSIs due to multidrug-resistant microorganisms (MDROs) and patients with catheter colonization by MDROs. Data from 86 patients admitted consecutively to a tertiary-care hospital from 2017 to 2020 were retrospectively analyzed. The mean dwell time was 25.73 ± 16.19 days in the PICC-CLABSI group and 16.36 ± 10.28 days in the PICC-colonization group (p = 0.002). The mean dwell time was 17.38 ± 9.5 days in the PICC-MDRO group and 22.48 ± 15.64 days in the PICC-non-MDRO group (p = 0.005). Within the PICC-CLABSI group, the mean dwell time for CLABSIs caused by MDROs was 21.50 ± 12.31 days, compared to 27.73 ± 16.98 days for CLABSIs caused by non-MDROs (p = 0.417). Within the PICC-colonization group, the mean dwell time was 15.55 ± 7.73 days in PICCs colonized by MDROs and 16.92 ± 11.85 days in PICCs colonized by non-MDROs (p = 0.124). The findings of the present study suggest that CLABSIs caused by MDROs in PICCs are associated with a shorter mean catheter dwell time compared to those caused by non-MDROs, underscoring the importance of considering infections by MDROs when evaluating PICC dwell times.